Electrical Energy Audit at Faculty of Computer Science and Information Technology, Universiti Tun Hussein Onn Malaysia - Azizan, Muhammad Rifqi Aiman; Mohd Yousof, Mohd Fairouz (Evolution in Electrical and Electronic Engineering, 2023)
Electrical Energy Audit is one of the methods that can be used to analyze the energy consumption of electrical equipment that is operated in the building and the possibility to reduce the energy consumption. There is some research from the previous studies and the results have been obtained through the implementation of this project. The scope of this project is to determine the illumination level of light, temperature, humidity, and thermal energy that may cause the occurrence of an increase in energy consumption in the Faculty of Computer Science and Information Technology, Universiti Tun Hussein Onn Malaysia. This project conducted by walkthrough audit of the building by measuring and recording the data. To facilitate the process of a walkthrough audit in the building, the floor plan of the building was required to plan and determine the area that was suitable to collect the data. Besides that, to get data for each type of measurement. It will use different methods and equipment such as Datalogger (measure temperature and humidity) and lux meter (measure illuminance level of light). From the analysis of the findings, the Energy Saving Measure (ESM) would propose to reduce electrical energy consumption for the building. Furthermore, providing ESM can assist in increasing energy efficiency and energy savings in this building, notably in terms of power bill prices. Indirectly, this audit can reduce energy waste and improve the stability of the local electrical supply system.